Conjugate Addition of Indoles and Pyrroles to Dihydronitronaphthalenes in Water: Synthesis of 3, 4‐Fused Tetrahydro‐β‐carbolines. Issue 4 (14th December 2012) - Malhotra, Rajesh; Ghosh, Rajib; Dey, Tushar K.; Chakrabarti, Sagar; Ghosh, Amit; Dutta, Swarup; Asijaa, Sonika; Roy, Subho; Dutta, Shantanu; Basu, Sourav; Hajra, Saumen
Abstract: A catalyst‐free conjugate addition of indoles and pyrroles to 1, 2‐dihydro‐3‐nitronaphthalenes in water has been developed. A variety of indoles containing electron‐rich and ‐deficient functional groups including aza‐indoles and pyrroles reacted smoothly with a number of dihydro‐3‐nitronaphthalenes, especially bromo derivatives. For structural elaboration, the bromo functionality (dihydronitronaphthalene unit as well as indolyl unit) of the addition products was utilized for Suzuki coupling reactions and provided moderate to good yields of the desired coupling compounds. The utility of the method was further demonstrated by the synthesis of 3, 4‐fused tetrahydro‐β‐carbolines, a new class of compounds, from the addition products through reduction of the nitro group to the amine and subsequent Pictet–Spengler cyclization. Abstract : A catalyst‐free conjugate addition of indoles and pyrroles to 1, 2‐dihydro‐3‐nitronaphthalenes in water provides 1‐heteroaryl‐2‐nitrotetralins with moderate to good diastereoselectivity and yields. The utility of the method was demonstrated by Suzuki coupling of the bromo functionality of the adducts and the synthesis of 3, 4‐fused tetrahydro‐β‐carbolines, a new class of compounds.